Tingkat Toleransi Antaragama di Masyarakat Indonesia - Binsar Antoni Hutabarat; H. Hans Panjaitan (Societas Dei: Jurnal Agama dan Masyarakat, 2016)
ABSTRACT: This article will measure the level of religious tolerance ini Indonesia. The measurement of this level of tolerance is based upon views of some students' organization in Jakarta. These samples are chosen because they are groups wich have most involvement in the issue of religious relationship. The samples wich are used to represent the population of students' organizations are five religious related organization, namely: Christian Student Movement of Indonesia (GMKI), Islam Students Community (HMI), Buddhist Students Community of Indonesia (HIKMAHBUDHI), Hindu Dharma Students Union of Indonesia (KMHDI), and Catholic Students Unity of the Republic of Indonesia (PMKRI). The views of these students' organizations are expected to be measurement tools for the level of religious tolerance in Indonesia society, wich are very important to preserve the integrity of Indonesia as a nation. Data collection in this research uses surveys in the form of Likert scale, as well as structured interview. Data analysis is done with triangulation method so that it is expected that data validity can be well preserved. KEYWORDS: tolerance, religion, violence